The Effect of CSR Disclosure on Company Performance With Ceo Proficiency As A Moderation Variable - Findy Rachmandika Muhammad; Sutrisno T; Muhammad Tojibussabirin (Publikasi Indonesia, 2023)
This study aims to examine the impact of corporate social responsibility (CSR) on the financial performance of manufacturing companies in Indonesia and examine the role of CEO ability as moderating variable. Hierarchical regression analysis is used to test the effect of CSR on firm performance and test CEO ability as moderating variable. This study uses 213 samples observation data from manufacturing companies listed on Indonesia Stock Exchange (IDX) during 2019 until 2021. The results showed that CSR disclosures has an effect on firm performance as measured by return on assets (ROA). The results of this study also showed that CEO ability as moderating variables unable to increase the influence of CSR on firm performance. These results indicate that when firm performance has no significant growth and firm has problem that decreased the firm profitability for example COVID-19 pandemic, CEOs have a tendency not to carry out an activity that costs money for example CSR.